Micro Waqf Bank Innovation Models in Aceh - Harianto, Syawal; Ramadhan, Muhammad; Soemitra, Andri (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
This study investigates the challenges and opportunities associated with utilizing cash waqf to support economic development in Aceh, Indonesia, employing the innovative Micro Waqf Bank model. Data was collected through in-depth interviews with seven Waqf management experts in Aceh, selected using purposive sampling. Leveraging the Analytical Network Process (ANP), the study identifies key problems in the development of cash waqf practices, including economic challenges such as capital sourcing, financing repayment delays, and monitoring-mentoring costs. From a social perspective, the study emphasizes the importance of synergy among institutions, public awareness, and effective socialization. Institutional issues include human resource professionalism, regulatory suitability, Micro Waqf Bank limitations, and the need for digitalization. Legal and governance aspects focus on regulations supporting capital financing for small enterprises and efficient managerial management. The study proposes an inclusive, adaptive, participatory, and integrated Micro Waqf Bank Innovation Model to optimize cash waqf utilization and support real sector economic growth. Suggestions for improvement involve technological infrastructure, human resource training, regulatory adjustments, capital management, monitoring systems, strategic partnerships, socialization, coordination, product diversification, and community participation, providing a comprehensive model for the development of Micro Waqf Banks in Aceh.==============================================================================================================ABSTRAK – Model Inovasi Bank Wakaf Mikro di Aceh. Penelitian ini mengkaji tantangan dan peluang pengembangan praktik wakaf tunai untuk mendukung pembangunan ekonomi di Aceh melalui model inovasi Bank Wakaf Mikro di Aceh. Data penelitian dikumpulkan melalui wawancara mendalam dengan tujuh pakar bidang manajemen wakaf di Aceh, yang dipilih dengan metode sampling purposif. Hasil analisis aplikasi Analytical Network Process (ANP), penelitian ini mengidentifikasi sejumlah persoalan kunci dalam pengembangan wakaf tunai, seperti tantangan ekonomi terkait sumber modal, keterlambatan pembayaran pembiayaan, dan biaya pemantauan/ mentoring. Secara sosial, kajian ini menggarisbawahi pentingnya sinergi antar lembaga, kesadaran masyarakat, dan sosialisasi. Aspek institusional melibatkan isu-isu seperti profesionalisme sumber daya manusia, regulasi yang sesuai, keterbatasan Bank Wakaf Mikro, dan digitalisasi. Aspek hukum dan tata kelola berfokus pada regulasi yang mendukung, pembiayaan modal untuk usaha mikro dan ultra-mikro, dan manajemen manajerial. Solusi telah diidentifikasi untuk setiap aspek, mencapai proposal model Inovasi Micro Waqf Bank yang inklusif, adaptif, partisipatif, dan terintegrasi untuk mengoptimalkan pemanfaatan waqf tunai dan mendukung pertumbuhan ekonomi sektor riil. Saran untuk perbaikan melibatkan infrastruktur teknologi, pelatihan sumber daya manusia, penyesuaian regulasi, manajemen modal, sistem pemantauan, kemitraan strategis, sosialisasi, koordinasi, diversifikasi produk, dan partisipasi masyarakat, sehingga memberikan model komprehensif untuk pengembangan Bank Wakaf mikro di Aceh.